1994
DOI: 10.1007/bf01982185
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of the human brucellosis vaccine and the intradermal reaction test for brucellosis

Abstract: The aim of the present study was to determine the tolerance and efficacy of human brucellosis vaccine as well as the tolerance and sensitivity of the intradermal reaction test for brucellosis. A total of 1,121 subjects initially consented to participate in the study. Following clinical examination, 762 were tested with the intradermal reaction test (IDR Test, Pasteur Merieux, France), of whom 576 with no previous or current brucellosis infection were accepted for vaccination. Two hundred seventy-one were vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…The French experience with a vaccine utilizing a phenolinsoluble peptidoglycan fraction of B. melitensis strain M-15 raised questions in the past about its efficacy. The vaccine was administered in two subcutaneous doses and supposedly offered protection for a 2-year period [55]. Efficacy of other vaccines that could be considered for humans has been proven in animals: the various preparations include a lipopolysaccharide-protein conjugate, a purified protein antigen L7/L12, Cu-Zn SOD, and glyceraldehyde-dehydrogenase.…”
Section: Treatmentmentioning
confidence: 99%
“…The French experience with a vaccine utilizing a phenolinsoluble peptidoglycan fraction of B. melitensis strain M-15 raised questions in the past about its efficacy. The vaccine was administered in two subcutaneous doses and supposedly offered protection for a 2-year period [55]. Efficacy of other vaccines that could be considered for humans has been proven in animals: the various preparations include a lipopolysaccharide-protein conjugate, a purified protein antigen L7/L12, Cu-Zn SOD, and glyceraldehyde-dehydrogenase.…”
Section: Treatmentmentioning
confidence: 99%
“…The authors observed local pain after injection in 45.2% of subjects and systemic reactions in 5.0%; however, the clinical efficacy of the vaccine could not be evaluated due to an insufficient number of participants. Lastly, in 1994, Hadjichristodoulou et al conducted a clinical trial on 271 volunteers in Greece; although the S19 vaccine caused some side effects in a quarter of subjects, it was considered safe enough for use on a large scale [ 41 ]. Nonetheless, there is currently no licensed anti- Brucella vaccine for humans.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed local pain after injection in 45% of subjects and systemic reactions in 5%; however, the clinical efficacy of the vaccine could not be evaluated due to an insufficient number of participants. Lastly, in 1994, Hadjichristodoulou et al conducted a clinical trial on 271 volunteers in Greece; although the S19 vaccine caused some side effects in a quarter of subjects, it was considered safe enough for use on a large scale (23). Nonetheless, there is currently no licensed anti- Brucella vaccine for humans.…”
Section: Discussionmentioning
confidence: 99%